THE ANALYSIS OF CADETS’ SPEAKING ANXIETY IN MORNING SPEECH PERFORMANCE - Siregar, Muhammad Sapril; Kusturi, Nanda Afra; Dahlan, Muhammad Harris H; Kartayuda, Arnoldus (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pelayaran Malahayati, 2021)
This study aims to determine how the level of anxiety of Cadets in speaking English during Morning Speech, what are the obstacles faced by Cadets in speaking English during Morning Speech, How the cadets solve the obstacles in speaking English during Morning Speech. This research was conducted at the Malahayati Merchant Marine Polytechnic. The participants of the study were 40 cadets from various majors, nautical, technical, and ETO. Data collection in this study was descriptive quantitative by distributing questionnaires and interviews with cadets who had carried out Morning Speech. The results showed that from 40 respondents in this study the highest is in moderate level with 35%. At the second level of anxiety is moderately high level with 25%. The low and high levels have an equal score with 17.5%. This is evidenced by a modified questionnaire assessment from McCroskey, J.C. In addition, the obstacles faced by Cadets in speaking English during the Morning Speech were anxiety, pounding, irregular breathing, nervousness when saying morning speech in front of friends, not often speaking in public, stage fright, fear of friends' opinions or lecturers, do not master the material, and the last result was how the cadets solve the obstacles faced in speaking English during the Morning Speech. There was convincing themselves confidently, trying to calm down and control themselves, by repeating before presenting a morning speech with friends at the dormitory, looking for materials and understanding the material that will be delivered during the morning speech, not showing friends that they are nervous, staring at the viewers' eyes by convincing myself psychologically that I can beat them, that I am better than them, asking for help to Miss / Mam in English to practice correct pronunciation, repeating the material until I can remember, and thinking positively.